Usulan Perbaikan Tata Letak Fasilitas Berbasis Alur Produksi dan Potensi Bahaya pada Unit Produksi MG Airguns - Firman Alamsyah; Difa Pratama Abdul Baits; Izzatin Aulia Rahmah; Dimas Pradyatama Falufy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
MG Airguns is an airgun manufacturing unit operating a make-to-order production system that requires an efficient and safe facility layout. The existing layout does not support a smooth process flow, as shown by unstructured machine placement, long material-handling distances, and a high potential for workplace hazards. This study analyzes occupational health and safety (OHS) through Job Safety Analysis (JSA) and the OHS control hierarchy, and redesigns the facility layout using the Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Material Handling Cost (OMH). The feasibility of the proposal was evaluated using Net Present Value (NPV) and Internal Rate of Return (IRR). The results show that the proposed layout reduces total material handling cost by 37.3% and separates hazardous work zones, while the economic analysis yields a positive NPV of IDR 2,011,476,700.91 and an IRR of 42%, indicating that the proposal is feasible to implement.